(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Industrial structures, residential buildings and other objects of infrastructure are being constructed in many Russian cities now. In addition to new constructions, reconstruction and rebuilding of existing buildings is also being performed. Meanwhile, such construction objects are situated not only in open suburban areas but also in urban districts and city zones. Often it is necessary to dismantle or demolish old run-down buildings or distressed structures before constructing new buildings. Such works always cause large amounts of construction waste. To accommodate constructive materials for new structures and to store elements of disassembled buildings and construction wastes special storage grounds are used. Being of temporal nature, these storage grounds are not capable to ensure full protection of the environment from pollution. The team of employees of Samara State Technical University investigated several districts of the city of Samara. This investigation revealed that in all temporary dumping sites construction wastes amount to 8% and dumping sites of a mixed type containing construction wastes – to 35%. The majority of temporary dumping sites are removed in a short time. Mostly, it is done by collection and removal of construction waste to special waste landfills. At the same time, the investigation demonstrated that though these dumping sites are temporal, their existence causes environmental pollution of underlying open ground as repugnant substance penetrates the ground with rains and pollution of airspace as light pollutants are dispersed by wind. Moreover, even after these temporary dumping sites are removed, already polluted soil layers continue to pollute soils as a secondary pollutant source. The authors offer a technical solution which allow to carry out rehabilitation of polluted urban areas more effectively. In particular, it is recommended to remove waste from the temporary dumping sites stage by stage. At the first stage, off-site areas should be inspected and the extent of pollution (pollution depth) of underground layers should be estimated. At the next stage, a protective barrier in the ground around the dumping site and on the surface should be built. Only after that we recommend that wastes should be removed and sent to a waste recycling plant or to a specially equipped waste landfill. Then, it is required to cut off all polluted soils and to remove them to a special waste landfill for storage. Thus, this solution makes it possible to reduce the risk of secondary environmental pollution.